THE EDUCATION CURRICULUM SYSTEM OF BOARDING SCHOOL - Rizal MZ, Syamsul (Tawazun: Jurnal Pendidikan Islam, 2018)
Amendment the model and the education system in boarding school is a response to the modernization of Islamic education and social change in society. One of renewal is a renewal of methodologies, such as the leveling system, institutional reform. In addition, the curriculum and the addition of subjects in boarding school was introduced. Enrichment and changes in the education curriculum of boarding school to seek a balance between the curriculum of religious knowledge and general knowledge. The effort is also to connect the differences ability and to support the society needs. However, sometimes the effort of education modernization in boarding school not always run well, so that more compromising the purity of boarding school curriculum. This research was conducted with the aim of knowing the education curriculum system of the boarding school, and determine how the efforts of the boarding school institutions in curriculum development and discover how the ideal curriculum system for boarding school institutions today. The research looked at the percentage of the highest number of students from various boarding schools. The approach used in this study is qualitative research with the inductive data analysis, does not start from the hypothesis, but instead looking for the data and real fact. The method that used by the researcher is a survey method, to ask, analyze, photograph and construct a situation that becomes the object of the research. Keywords : curriculum, boarding school, teaching method